Interobserver evaluation of TLICS system to treat thoracolumbar fractures - Bernardo José Moreira Chaves (Coluna/Columna, 2015)
OBJECTIVE: To evaluate the interobserver agreement regarding the TLICS Classification (Thoracolumbar Injury Classification and Severity Score). Furthermore, evaluate the reliability, analyzing the correlation between the treatment indicated by TLICS system (surgical or conservative) and the treatment indicated by each evaluator surgeon. METHODS: Imaging tests and clinical data of 22 patients with thoracolumbar fractures were analyzed by eight spine surgeons, and two main analyzes were performed: the first compared the interobserver agreement related to TLICS and the second compared the agreement between the treatment indicated by TLICS classification (surgical or conservative) and treatment indicated by each surgeon - based on his personal experience and the preferred classification. RESULTS: Using the parameters of Landis and Koch for interpretation of Kappa value, the interobserver agreement of TLICS classification was considered moderate in our study (K=0.6). The agreement between the indications of treatment (surgical or conservative) dictated by the classification and the indication of each surgeon was considered excellent, with kappa value of 0.89. CONCLUSION: We believe that the classification is a good tool for the evaluation and the treatment indication in thoracolumbar fractures.